Pauline Baptism among the mysteries: ritual messages and the promise of initiation - Jeong, Donghyun (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2023)
The series Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft (BZNW) is one of the oldest and most highly regarded international scholarly book series in the field of New Testament studies. Since 1923 it has been a forum for seminal works focusing on Early Christianity and related fields. The series is grounded in a historical-critical approach and also explores new methodological approaches that advance our understanding of the New Testament and its world.